#### Answer

vertical asymptotes: $x=1/3$, $x=-1$
horizontal asymptote: $y=2/3$

#### Work Step by Step

To first find out the vertical asymptotes, we can take the denominator of the function and factor it out into $(3x-1)(x+1)$. By solving for y=0, we come up with the vertical asymptotes of $x=1/3$, $x=-1$.
To find our horizontal asymptotes, we can take the coefficients of the highest degree in each polynomial. Because both of these are of the second degree, we can divide them to yield $2x^{2}/3x^{2}$ to get an asymptote at $y=2/3$